Delineating origins of cheetah cubs in the illegal wildlife trade: Improvements based on the use of hair δ18O measurements - Koehler, Geoff; Schmidt-Küntzel, Anne; Marker, Laurie; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2023)
All African felids are listed as vulnerable or endangered according to the IUCN (International Union for Conservation of Nature) Red List of Threatened Species. Cheetahs Acinonyx jubatus) in particular have declined rapidly as a result of human impacts so that development of effective strategies and tools for conservation of this highly vulnerable species, as well as African felids in general, are essential for their survival in the wild. Here we use the oxygen stable isotopic compositions of cheetah hair to determine origins of cheetah cubs destined for the illegal exotic pet trade by associating individual cubs with predicted δ18O isoscape locations. We found that cheetah cubs most likely originated in East Africa, close to the corridors responsible for this aspect of the illegal wildlife trade to the Middle East. Further refinement of these assignments using a two isotope analysis (δ18O and δ13C values) indicate that these cubs were likely sourced in Southern Ethiopia or possibly as far as Tanzania. We also demonstrate that δ18O values in tissues can provide provenance information in cases where results of δ2H analyses may be obscured by the effects of metabolic routing of nutrients during nursing, starvation, or dehydration. This study demonstrates the utility of stable isotopic tools for conservation and forensic uses for endangered mammalian species.